The correlation between retinal microvascular changes by optical coherence tomography angiography and nailfold capillaroscopic findings in patients with systemic sclerosis - Sahar Abd-Elrahman Elsayed; Amr Mounir; Engy Mohamed Mostafa; Dalia Salah Saif; Ola Mounir (Journal of Rheumatic Diseases)
Objective: We aimed to detect the correlation between retinal microvascular changes by optical coherence tomography angiography (OCTA) and nailfold capillaroscopic findings in patients with systemic sclerosis (SSc).Methods : : Forty SSc patients and thirty healthy controls were included. A complete history was taken, general and rheumatological examination and laboratory investigations were performed. In addition, all the participants were examined using nail fold capillaroscopy (NFC) and OCTA.Results : : Our patients have decreased nailfold capillary density, central macular thickness, superficial full vessel density (VD), superior, inferior, and medial superficial peri-foveal VD, superior, inferior, and temporal superficial parafoveal VD, and temporal para-foveal full VD compared to the controls. The modified Rodnan skin score was negatively correlated with the nail fold capillary density, central macular thickness, superficial full VD, superior, temporal, and medial superficial perifoveal VD, superior superficial parafoveal VD, and temporal perifoveal full VD. The nailfold capillary density was positively correlated with the central macular thickness, the superficial full VD, the superior, temporal, and medial superficial perifoveal VD, the superior superficial parafoveal VD, and temporal perifoveal full VD.Conclusion : : The nailfold capillary density measured by NFC positively correlates with the retinal VD measured by OCTA, suggesting that NFC could be a valuable marker for retinal vessel involvement in SSc patients. In addition, our results highlight the importance of combining OCTA with NFC for diagnosing and monitoring microvascular changes in SSc patients.